The effect of water-based exercises on balance in persons post-stroke: a randomized controlled trial. Issue 4 (19th May 2017) - Chan, Kelvin; Phadke, Chetan P.; Stremler, Denise; Suter, Lynn; Pauley, Tim; Ismail, Farooq; Boulias, Chris
Abstract: Objective: Water-based exercises have been used in the rehabilitation of people with stroke, but little is known about the impact of this treatment on balance. This study examined the effect of water-based exercises compared to land-based exercises on the balance of people with sub-acute stroke. Methods: In this single-blind randomized controlled study, 32 patients with first-time stroke discharged from inpatient rehabilitation at West Park Healthcare Centre were recruited. Participants were randomized into W (water-based + land; n = 17) or L (land only; n = 15) exercise groups. Both groups attended therapy two times per week for six weeks. Initial and progression protocols for the water-based exercises (a combination of balance, stretching, and strengthening and endurance training) and land therapy (balance, strength, transfer, gait, and stair training) were devised. Outcomes included the Berg Balance Score, Community Balance and Mobility Score, Timed Up and Go Test, and 2 Minute Walk Test. Results: Baseline characteristics of groups W and L were similar in age, side of stroke, time since stroke, and wait time between inpatient discharge and outpatient therapy on all four outcomes. Pooled change scores from all outcomes showed that significantly greater number of patients in the W-group showed improvement post-training compared to the L-group ( p < 0.05). More patients in W-group showed change scores exceeding the published minimal detectable change scores. Discussion: A combination of water- and land-based exercises has potential for improving balance. The results of this study extend the work showing benefit of water-based exercise in chronic and less-impaired stroke groups to patients with sub-acute stroke.